Treatment outcome of vocal cord leukoplakia by transoral laser microsurgery. Issue 1 (January 2017) - Yang, Shih-Wei; Chao, Wei-Chieh; Lee, Yun-Shien; Chang, Liang-Che; Hsieh, Tsan-Yu; Chen, Tai-An; Luo, Cheng-Ming
Abstract The aim of this study is to evaluate the treatment outcome and analyze the associated factors of postoperative recurrence in patients who received transoral laser microsurgery for vocal cord leukoplakia. The demographic, histopathological data were retrospectively reviewed and the factors associated with recurrence of vocal leukoplakia after surgery were analyzed statistically. A total of 44 patients, including 36 males and 8 females, with a mean age of 50.4 ± 13.4 years, were enrolled. All the patients received excision of the vocal leukoplakia by carbon dioxide laser (2–4 Watt, ultrapulse mode) under general anesthesia. No patients had malignant transformation after surgery. Postoperative recurrence occurred in 10 patients (22.7 %). Univariate analysis showed that patients who had the habit of cigarette smoking, alcohol drinking, and presence of gastroesophageal reflux disease tended to recur. Among these risk factors, presence of gastroesophageal reflux disease (odds ratio 8.43) was the independent prognostic factor for recurrence using multivariate logistic regression analysis. Carbon dioxide laser excision is effective for treating vocal leukoplakia that is still confined to dysplasia of any degree, with acceptable morbidity. This study suggests that the presence of gastroesophageal reflux disease is the prognostic indicator for postoperative recurrence of vocal leukoplakia. Aggressive treatment of reflux disease for those who have received surgical excision for vocal leukoplakia is indicated.